1996
DOI: 10.1139/z96-101
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the use of hard parts in faeces to identify harbour seal prey: results of captive-feeding trials

Abstract: Faeces were collected from four captive harbour seals (Phoca vitulina) that consumed known amounts of herring (Clupea harengus), walleye pollock (Theragra chalcogramma), Pacific hake (Merluccius productus), surf smelt (Hypomesus pretiosus), and juvenile chinook salmon (Oncorhynchus tshawytscha). The goal was to determine which structures (hard parts) passed through the digestive tract (e.g., eye lenses, scales, vertebrae, otoliths), and which of these could be used to determine the type and number of fish cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 16 publications
1
67
0
1
Order By: Relevance
“…Traditionally, competition between pinnipeds and fisheries, and pinniped food habits have been evaluated through the visual analysis of fish sagittal otoliths and cephalopod beaks found in gut contents or fecal samples of pinnipeds (Harvey 1987, Cottrell et al 1996. Because otoliths can be partially or totally digested as they pass through the gut of seals (Dellinger & Trillmich 1988, Harvey 1989, Bowen 2000 size and frequency of prey can be underestimated (Dellinger & Trillmich 1988, Harvey 1989, Cottrell et al 1996, Bowen 2000, Orr & Harvey 2001.…”
Section: Data Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, competition between pinnipeds and fisheries, and pinniped food habits have been evaluated through the visual analysis of fish sagittal otoliths and cephalopod beaks found in gut contents or fecal samples of pinnipeds (Harvey 1987, Cottrell et al 1996. Because otoliths can be partially or totally digested as they pass through the gut of seals (Dellinger & Trillmich 1988, Harvey 1989, Bowen 2000 size and frequency of prey can be underestimated (Dellinger & Trillmich 1988, Harvey 1989, Cottrell et al 1996, Bowen 2000, Orr & Harvey 2001.…”
Section: Data Limitationsmentioning
confidence: 99%
“…Because otoliths can be partially or totally digested as they pass through the gut of seals (Dellinger & Trillmich 1988, Harvey 1989, Bowen 2000 size and frequency of prey can be underestimated (Dellinger & Trillmich 1988, Harvey 1989, Cottrell et al 1996, Bowen 2000, Orr & Harvey 2001. When prey structures in addition to otoliths were identified in fecal samples, frequency and number of individual prey were at least 2 times greater for many prey taxa (Olesiuk 1993, Cottrell et al 1996, Lance et al 2001, Browne et al 2002. Cartilaginous fishes may be underestimated in the diet if their statoconia were completely digested before excretion (Everitt & Gearin 1981).…”
Section: Data Limitationsmentioning
confidence: 99%
“…Boyle et al, (1990) reported that during a captive feeding experiment they recovered only 1 salmon otolith out of a total of 38 ingested (2.6% recovery rate). Cottrell et al (1996) reported an average recovery rate of 54 % for otoliths of several species of fish fed to captive harbour seals. They also found that using bone structures other than otoliths significantly improved the detection of prey species and concluded, 'identifying several different prey structures increases the likelihood of identifying a prey type'.…”
Section: Rank Order Of Months: Aprmentioning
confidence: 99%
“…These prey fragments are usually recovered from scats collected at seal haul-out sites (e.g., Härkönen 1987;Prime and Hammond 1990;Hammond et al 1994;Tollit and Thompson 1996) or retrieved from the contents of stomachs and intestines of dead animals (e.g., Lowry et al 1980;Finley and Gibb 1982;Gjertz and Lydersen 1986;Bowen et al 1993;Weslawski et al 1994;Hjelset et al 1999). Analyses of hard parts provide important information about diet, but these methods have inherent, well-recognized biases (see da Silva and Neilson 1985;Jobling and Breiby 1986;Dellinger and Trillmich 1988;Harvey 1989;Gales and Cheal 1992;Cottrell et al 1996). Firstly, hard-part analyses are usually based on scats collected on shore or stomachs collected from seals shot near haul-out areas.…”
Section: Introductionmentioning
confidence: 99%